A New Species of Daemonorops (Arecaceae) from Sekundur Forest, North Sumatra - Himmah Rustiami; Zumaidar Zumaidar (Floribunda, 2002)
Jenis baru Daemonorops (Arecaeae) dari hutan Sekundur, Sumatra Utara.